Strategi Diferensiasi dan Positioning dalam Memotivasi Nasabah Menabung pada Tabungan Barokah di BPRS Bhakti Sumekar Cabang Pamekasan - Susmiati Susmiati (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2016)
The development of Syari’a banking is rapidly make the level of competition is getting tighter. Whereas the products offered by each banking institutions are not much different. Therefore, the banks should have a distinctive difference in the products of competitors, so that customers have a reason to make a choice in selecting a product offered by these banks. Efforts can be done applying the strategies of differentiation and positioning. The purpose of this research, first: researcher wants to know how to influence the strategy of differentiation and positioning in motivating customers to save for Barokah savings in BPRS Bhakti Sumekar of Pamekasan branch; second, researchers want to know the most dominant factor in motivating customers to save for Barokah savings in BPRS Bhakti Sumekar of Pamekan branch. This study uses a quantitative approach, with multiple linear regression analysis techniques. This data type is a primary data obtained through questionnaires. Respondents are a number of clients BPRS Bhakti Sumekar of Pamekasan branch that use the barokah savings. The results of this research indicate that based on the results of linear regression analysis obtained equation Y = 0,094 + 0,315X1 + 0,663X2, this equation states without differentiation and positioning strategies, customers motivation save for Barokah savings amounted to 0,094 and every enhancement of 1% for strategy of differentiation and positioning will lead to an enhancement amounted to 0,315 and 0,663 on the customer’s motivation to save for Barokah savings. The strategy contributions of differentiation and positioning is quite high with a value of determination coefficient amounted to 0,669 or 66,9%, which means that 66,9% of variation from motivation customers to save for Barokah savings explained by the strategy variation of differentiation and positioning while the remaining 33,1% is explained by the other factors variation are not included in this research. Based on the results of testing the hypothesis with T and F test shows the significant value of 0,000 which means that the strategy of differentiation and positioning a significant effect to the customer’s motivation to save for Barokah savings in BPRS Bhakti Sumekar of Pamekasan branch. While most dominant variable in influencing the customer’s motivation to save on Barokah savings is positioning variable with a value of determination coefficient amounted to 0,663 or 66,3% and the value of the T test of 8,130 or 81,30%.